(untitled) (Swiss Medical Weekly, 2012)
Abatacept (CTLA-Ig), a modulator of T-lymphocyte activation, has been approved by the Swiss health regulatory agency Swissmedic for the treatment of active rheumatoid arthritis (RA). This article summarises the key trial findings for this biologic agent in RA in different situations such as early erosive rheumatoid arthritis (RA), biologic-naïve RA, RA before and after the use of methotrexate or TNF-inhibitors and includes safety information from these trials. Based on these data, recommendations for clinical practice in Switzerland are made by a panel of experts.